2014
DOI: 10.1097/sla.0000000000000259
|View full text |Cite
|
Sign up to set email alerts
|

Improving ATLS Performance in Simulated Pediatric Trauma Resuscitation Using a Checklist

Abstract: Implementing a checklist during simulated pediatric trauma resuscitation improves adherence to the ATLS protocol without increasing the workload of trauma team members.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 25 publications
1
26
0
1
Order By: Relevance
“…This current study is a secondary analysis of the simulations performed for this study 29. The IRB approved the previous study and secondary analyses such as this one were also included in that IRB.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This current study is a secondary analysis of the simulations performed for this study 29. The IRB approved the previous study and secondary analyses such as this one were also included in that IRB.…”
Section: Methodsmentioning
confidence: 99%
“…The 12 teams participated in four scenarios 29. In each scenario, the teams had to identify and manage two potentially life-threatening injuries, including hypotension, pneumothorax, seizure and profound hypothermia.…”
Section: Methodsmentioning
confidence: 99%
“…Our current system uses a black text color for unchecked items and 30% opacity for items that are checked. It was important to deemphasize items that are checked because prior research has found that people often check items before task completion, in anticipation that the task will be performed [14]. They then end up skipping the task or performing it, but forgetting to check it off.…”
Section: From Paper To Digital Formatmentioning
confidence: 99%
“…To assist with memory recall of procedural items in settings with high cognitive load, clinicians have used mnemonics when designing protocols (e.g., “ABC” for “Airway, Breathing, Circulation” in resuscitation), but even these strategies are prone to error [5]. Drawing from experiences with checklists in other safety-critical domains such as aviation, researchers have designed a trauma resuscitation checklist as an alternative approach to improving team performance [14]. This paper-based checklist contains a total of 65 items grouped into four sections: pre-arrival plan, primary survey, secondary survey and prepare for travel (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the complex and high-stress nature of this environment, medical errors are common [4], leading to adverse patient outcomes. Recent implementation of checklists [5] and other decision support systems [1], however, has shown improved protocol adherence and reduced errors. Checklists are cognitive aids designed to reduce human errors and cognitive workload.…”
Section: Introductionmentioning
confidence: 99%